AL – BANJARI HADRAH MUSIC LEARNING IN THE SUKAROL MUNSYID GROUP AT AL – FALAH ISLAMIC BOARDING SCHOOL, MOJOKERTO CITY - Agustine, Rismi Sekar; Yanuartuti, Setyo (Solah, 2025)
The Al-Banjari Hadrah learning conducted by the Sukarol Munsyid Group aims to understand the forms of learning, including methods and outcomes in Al-Banjari Hadrah music education. Qualitative approach methods in research were employed to comprehend the learning process through observation, interviews, literature review, and documentation. The research results indicate that the learning objectives of Al-Banjari Hadrah in the Sukarol Munsyid Group are to preserve the art of Al-Banjari Hadrah and maintain the existence of the Sukarol Munsyid Group. The methods employed include training, peer tutoring, demonstration, and imitation. The learning materials consist of popular Islamic hymns, including "Nurul Mustofa," presented as a final work uploaded to the "Suka Sukarol Munsyid" YouTube channel. Learning components include flying instruments, bass drums, and vocals. Evaluation is conducted on a micro and macro scale, with evaluation indicators covering cognitive, affective, and psychomotor domains. The learning process is well-executed to achieve optimal learning outcomes, thereby proving the current level of achievement and existence. Bagian Atas Formulir Keywords: Learning, Hadrah Al-banjari, Sukarol Munsyid